2018
DOI: 10.1073/pnas.1809868115
|View full text |Cite|
|
Sign up to set email alerts
|

Earth’s outgoing longwave radiation linear due to H2O greenhouse effect

Abstract: Satellite measurements and radiative calculations show that Earth’s outgoing longwave radiation (OLR) is an essentially linear function of surface temperature over a wide range of temperatures (≳60 K). Linearity implies that radiative forcing has the same impact in warmer as in colder climates and is thus of fundamental importance for understanding past and future climate change. Although the evidence for a nearly linear relation was first pointed out more than 50 y ago, it is still unclear why this relation i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
217
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 127 publications
(240 citation statements)
references
References 39 publications
21
217
2
Order By: Relevance
“…The ERA+RRTM sensitivity is broken down into contributions from water vapor ( normalΔOLRH2normalOnormalΔTs=1.951emW m2K1, negative of equation (7b)'s respective term), atmospheric temperature ( normalΔOLRTanormalΔTs=2.701emW m2K1, negative of equation (7b)'s respective term), and surface temperature ( normalΔOLRTsnormalΔTs=1.271emW m2K1). Koll and Cronin () used an idealized atmospheric column and showed that there was a near‐perfect cancelation between the contributions from water vapor and atmospheric temperature to the feedback parameter, and only surface temperature contributes. However, in our ERA+RRTM calculations with real atmospheric conditions for columns across Earth, we show that this cancelation is imperfect with a 37% ( 2.701.952.02) contribution from atmospheric temperature to the total feedback parameter.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The ERA+RRTM sensitivity is broken down into contributions from water vapor ( normalΔOLRH2normalOnormalΔTs=1.951emW m2K1, negative of equation (7b)'s respective term), atmospheric temperature ( normalΔOLRTanormalΔTs=2.701emW m2K1, negative of equation (7b)'s respective term), and surface temperature ( normalΔOLRTsnormalΔTs=1.271emW m2K1). Koll and Cronin () used an idealized atmospheric column and showed that there was a near‐perfect cancelation between the contributions from water vapor and atmospheric temperature to the feedback parameter, and only surface temperature contributes. However, in our ERA+RRTM calculations with real atmospheric conditions for columns across Earth, we show that this cancelation is imperfect with a 37% ( 2.701.952.02) contribution from atmospheric temperature to the total feedback parameter.…”
Section: Resultsmentioning
confidence: 99%
“…Hallberg and Inamdar (1993) focused on surface temperatures above 298 K, where G was found to nonlinearly increase. Recently, Koll and Cronin (2018) showed a nonlinear decrease in clear sky OLR at high temperatures, which can also be characterized as SGE. Past work on SGE has been based on idealized models that used a single global mean column and did not account for RH variations (Dewey & Goldblatt, 2018).…”
Section: Supporting Informationmentioning
confidence: 99%
See 2 more Smart Citations
“…The linearization in Eq. 1 is justified, as Earth's outgoing longwave radiation does not follow classical Stefan-Boltzmann theory, but increases linearly with surface temperature (35) due to the watervapor feedback (36). A hypothetical jump in radiative forcing F by 1 W·m −2 will lead to global surface warming that reduces the PRI surplus until a balanced budget is reachieved again (3).…”
Section: Discussionmentioning
confidence: 99%